Content validity and reliability of instruments for evaluating culinary skills teaching factory programs - Niza, Niza; Istiyono, Edi; Setiawati, Farida Agus; Sumin, Sumin (Research and Social Study Institute, 2023)
This research aims to develop an evaluation instrument for the teaching factory (TEFA) program for culinary expertise competence at SMKN 6 Yogyakarta. Instruments developed based on the CIPP evaluation model (Context, Input, Process, Product). Research methods using instrument development stages refer to test development procedures according to Oriondo & Dallo-Antonio: (1) test design, (2) trials, (3) determination of validity, and (4) determination of reliability. The sample used was 120 class XI Culinary students for the academic year 2023/2024 in the environment of SMKN 6 Yogyakarta. Polytome data were analyzed withÂ the Partial Credit Model using the Quest program. The results showed that as many as ten items of evaluation instruments fit with the model. The reliability value of the instrument is 0.78. This means that the reliability of the instrument is in the high category. The results of content and construct validation state that all items (16 items) are suitable to be used to evaluate the culinary competence teaching factory (coffee shop) program at SMKN 6 Yogyakarta.Â Â